Sustaining large marine ecosystems the human dimension - Hennessey, Timothy M.; Sutinen, Jon G. (Amsterdam ; Boston : Elsevier, 2005)
The shift away from the management of individual resources to the broader perspective of ecosystems is no longer confined to academia and think tanks where it first began; the ecosystem paradigm also is beginning to take root in government policy and programs. This volume provides innovative and timely approaches for improving and sustaining socioeconomic benefits from LMEs. The authors describe methodologies and actions for moving forward in halting the downward resource sustainability spiral and advancing toward the recovery of depleted fish stocks, restoration of degraded habitats, and reduction and control of pollution within the framework of an ecosystem-based approach for the governance of LMEs. * First book to ever publish that focuses on the human dimension of large marine ecosystem management * Offers set of guidelines for possible interrelationship management programs * Addresses taxing issues and problems pertaining to the world's marine ecosystems * Provides a matrix of the interdependence of economic, social, cultural and governance elements.
The large marine ecosystem approach for assessment and management of ocean coastal waters / Kenneth Sherman -- The human dimension in ecosystem management : institutional performance and the sea grant paradigm / R. Baird -- A framework for monitoring and assessing socioeconomics and governance of large marine ecosystems / Jon G. Sutinen, Patricia Clay, Christopher L. Dyer, Steven F. Edwards, John Gates, Tom A. Grigalunas, Timothy Hennessey, Lawrence Juda, Andrew W. Kitts, Philip N. Logan, John J. Poggie Jr., Barbara Pollard Rountree, Scott R. Steinback, Eric M. Thunberg, Harold F. Upton and John B. Walden -- Governance profiles and the management of the uses of large marine ecosystems / Lawrence Juda and Timothy Hennessey -- A total capital approach to the management of large marine ecosystems : case studies of two natural resource disasters / Christopher L. Dyer and John J. Poggie -- Ownership of multi-attribute fishery resources in large marine ecosystems / Steven F. Edwards -- Economic activity associated with the northeast shelf large marine ecosystem : application of an input-output approach / P. Hoagland, D. Jin, E. Thunberg and S. Steinback -- Portfolio management of fish communities in large marine ecosystems / Steven F. Edwards, Jason S. Link and Barbara P. Rountree -- Fish habitat : a valuable ecosystem asset / Harold F. Upton and Jon G. Sutinen -- The economic values of Atlantic herring in the Northeast Shelf large marine ecosystem / Jung Hee Cho, John M. Gates, Phil Logan, Andrew Kitts and Mark Soboil --Eutrophication in the Northeast Shelf Large Marine Ecosystem : linking hydrodynamic and economic models for benefit estimation / Thomas A. Grigalunas, James J. Opaluch, Jerry Diamantides and Dong-Sik Woo -- Valuing large marine ecosystem fishery losses because of disposal of sediments : a case study / T.A. Grigalunas, J.J. Opaluch and M. Luo -- Emergence of a science policy-based approach to ecosystem-oriented management of large marine ecosystems / F.J. Gable -- Applications of the large marine ecosystem approach toward world summit targets / Alfred Duda and Kenneth Sherman -- The evolution of LME management regimes : the role of adaptive governance / Timothy M. Hennessey -- An evaluation of the modular approach to the assessment and management of large marine ecosystems / Hanling Wang -- Conclusion / Timothy Hennessey and Jon Sutinen.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Marine ecology -- Management; Marine resources -- Management; Ecosystem management; Ecosystem health -- Economic aspects -- Management; Electronic books